Avaliação da associação entre performance e padrões eletrooculográficos durante competição através de jogo eletrônico - Oliveira, Gabriel Barros Lins Lelis de (2022)
In this work, we propose to investigate, through electro-oculography (EOG) analysis, the relationship between the score obtained during an electronic game and eye movement. The EOG data and scores were collected from an experiment carried out with 32 subjects, who came to the laboratory in pairs to participate in a dispute through the game "F.E.A.R. Combat". Each pair was divided into two roles, prey and predator. Both could attack each other with punches, but the predator had the advantage of being able to attack using a shotgun. The prey's goal was to collect as many medical kits as possible and die as little as possible. For the predator, the objective was to kill the prey as many times as possible and avoid dying. The experiment was divided into three stages: Game 1, 2-hour nap and Game 2. During each stage, electroencephalography (EEG), EOG and electrocardiography (ECG) signals were being measured using electrodes fixed to the head. In addition, the scores obtained at the end of each game were collected. In this work, we will stick only to the analysis of the EOG data and the scores for the Game 1 and Game 2 stages. For the EOG data, computational analysis methods were used in the Python language, initially doing the pre-processing of these data, to then find two types of characteristic movements of electrooculographic signals: blinks and saccades. To detect these events, we use an open-source and semi-automatic algorithm. Spearman correlations between the total amount of ocular events and the scores obtained were evaluated. From this, we found two statistically significant correlations (p < 0.05). For prey we found a moderate negative correlation (Rs = -0.551) between saccade gain and attack score gain, indicating that players who hide more die more and move their eyes more. As for the predator, we found a moderate negative correlation (Rs = -0.416) between the gain of blinks and the gain of deaths, indicating that predators that start to die a lot start to find the game difficult, and, therefore, end up blinking less. to be able to focus more on the game.